2018
DOI: 10.1155/2018/7910754
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumours: Rise in Glioblastoma Multiforme Incidence in England 1995–2015 Suggests an Adverse Environmental or Lifestyle Factor

Abstract: Objective To investigate detailed trends in malignant brain tumour incidence over a recent time period. Methods UK Office of National Statistics (ONS) data covering 81,135 ICD10 C71 brain tumours diagnosed in England (1995–2015) were used to calculate incidence rates (ASR) per 100k person–years, age–standardised to the European Standard Population (ESP–2013). Results We report a sustained and highly statistically significant ASR rise in glioblastoma multiforme (GBM) across all ages. The ASR for GBM more than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 26 publications
3
93
1
1
Order By: Relevance
“…Our results of rising trend of glioblastoma incidence and trend variations by glioma histology subtypes are in line with previous findings in the United States and European countries. [27][28][29][30] The observed distinct period and birth cohort effect patterns of glioblastoma and nonglioblastoma could be due to a number of histology-specific factors that dynamically affect the population. However, these histology-specific factors are largely unknown or postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of rising trend of glioblastoma incidence and trend variations by glioma histology subtypes are in line with previous findings in the United States and European countries. [27][28][29][30] The observed distinct period and birth cohort effect patterns of glioblastoma and nonglioblastoma could be due to a number of histology-specific factors that dynamically affect the population. However, these histology-specific factors are largely unknown or postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a highly malignant grade IV astrocytoma. It is considered to be the most biologically aggressive brain tumour and is associated with a post diagnosis survival rate of only 1 year (Philips et al, 2018). GBMs display attributes of various morphologies such as a heterogeneous mixture of cells that demonstrate varying degrees of cellular and nuclear polymorphism, making it difficult to clinically manage.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to overcome these issues, research groups have identified numerous naturally derived bioactive compounds (NDBC) known as phytochemicals that demonstrate anticancer activity when used alone or in combination for the treatment of cancer (Philips et al, 2018). Phytochemicals with anti-cancer properties are being assessed as precursors for new chemotherapeutic agents (Koldaş et al, 2015;Neto, 2007;Øverby et al, 2014;Sasidharan et al, 2011;H.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid tumour growth is mainly related to deregulation of the G1/S checkpoint in the cell cycle and the occurrence of multiple genetic abnormalities of tumor cells [2,3]. However, the actual causes of these brain tumors in adults remain largely unknown [4]. At present, standard clinical treatment for GBM relies on surgery and chemo-radiation therapies [5].…”
Section: Introductionmentioning
confidence: 99%